2021
DOI: 10.1542/peds.2021-051261
|View full text |Cite
|
Sign up to set email alerts
|

Six Stages of Engagement in ADHD Treatment Described by Diverse, Urban Parents

Abstract: BACKGROUND Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental condition in children. Although ADHD is treatable, barriers remain to engagement in treatment, especially among socioeconomically disadvantaged and racial and ethnic minority families. Our goal was to examine the process by which families engage in ADHD treatment and to identify targets for an intervention to improve engagement in care. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Families of color report hesitation to disclose social needs and mental health concerns to primary care providers due to fear of shame, judgement, being reported to child welfare, and not being taken seriously, all rooted in health care mistrust due racism, which can impact the accuracy of screening results. 9 At the same time, we found that even after needs were disclosed in primary care, families of color were less likely to report their social needs were addressed than white families. 10 Overall, children of color have worse access to mental health care than white children, a disparity that may be widening due to COVID-19.…”
Section: Racismmentioning
confidence: 78%
“…Families of color report hesitation to disclose social needs and mental health concerns to primary care providers due to fear of shame, judgement, being reported to child welfare, and not being taken seriously, all rooted in health care mistrust due racism, which can impact the accuracy of screening results. 9 At the same time, we found that even after needs were disclosed in primary care, families of color were less likely to report their social needs were addressed than white families. 10 Overall, children of color have worse access to mental health care than white children, a disparity that may be widening due to COVID-19.…”
Section: Racismmentioning
confidence: 78%
“…Participants were parents of children and adolescents diagnosed with ADHD who previously enrolled in a qualitative study on engagement in ADHD care 9 and who were recruited for the original study between June 2018 and October 2019 from pediatric outpatient treatment settings at Boston Medical Center, an urban safety net hospital. The initial and new studies were approved by our institutional review board.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all parents (95%) reported more difficulty caring for their child during the pandemic because of difficulties with remote school (9), not being able to take their child outside (7), exacerbated behavioral symptoms (6), disrupted routine (1), and financial difficulties (1).…”
Section: Caregiver Burden During the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Need: Improved access to clinical services, support and financial assistance. Though some ADHD consumers in Hong Kong reported no challenges accessing health services (Cheung et al, 2015), consumers from 14 studies (60.9%) reported gaps relating to accessing appropriate clinical services, support and financial assistance (Cheung et al, 2015;Fridman et al, 2017;Ho, Chien, & Wang, 2011;Hossainzadeh Maleki et al, 2018;McIntyre & Hennessy, 2012;Nasol et al, 2019;Pahlavanzadeh et al, 2018;Reale et al, 2015;Rezel-Potts et al, 2021;Sikirica et al, 2015;Simons et al, 2016;Spencer et al, 2021;Swift et al, 2013;Vijverberg et al, 2020). Caregivers reported challenges obtaining an ADHD diagnosis due to long waiting periods and drawn out diagnostic processes, visiting multiple doctors, problems with misdiagnosis, insufficient resources and difficulty finding professionals that would listen (McIntyre & Hennessy, 2012;Rezel-Potts et al, 2021;Sikirica et al, 2015;Simons et al, 2016).…”
Section: Study Characteristicsmentioning
confidence: 99%